2008
DOI: 10.1002/cssc.200700152
|View full text |Cite
|
Sign up to set email alerts
|

Highly Dispersed Gold on Zirconia: Characterization and Activity in Low‐Temperature Water Gas Shift Tests

Abstract: Gold-loaded zirconia and sulfated zirconia catalysts were tested in the low-temperature water gas shift reaction. The samples were characterized by N2 adsorption analysis, temperature-programmed reduction, X-ray diffraction, pulse-flow CO chemisorption, FTIR spectroscopy, and high-resolution transmission electron microscopy. A reference catalyst, Au/TiO2, provided by the World Gold Council was investigated for comparison. CO chemisorption and FTIR data indicate the presence of only highly dispersed gold cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 41 publications
0
45
1
1
Order By: Relevance
“…It was found that the ZrO 2 /SO 4 = support after calcination contains a 2 wt% of sulfates. On the contrary, as previously reported [16,21], tests of sulfates carried out on the samples after deposition of gold, evidence that no sulfates are present in the final catalysts anymore. This is not unexpected, pointing out that the detachment of sulfate groups occurs during the deposition-precipitation, as a consequence of the basic conditions.…”
Section: Catalyst Characterizationcontrasting
confidence: 40%
See 2 more Smart Citations
“…It was found that the ZrO 2 /SO 4 = support after calcination contains a 2 wt% of sulfates. On the contrary, as previously reported [16,21], tests of sulfates carried out on the samples after deposition of gold, evidence that no sulfates are present in the final catalysts anymore. This is not unexpected, pointing out that the detachment of sulfate groups occurs during the deposition-precipitation, as a consequence of the basic conditions.…”
Section: Catalyst Characterizationcontrasting
confidence: 40%
“…These species coming from the Na 2 CO 3 used for the depositionprecipitation can occupy active sites on gold particles, thus worsening their ability to chemisorb CO molecules and their activities. Further catalytic tests have been performed on these catalysts to evaluate the stability of the Au/ZrO 2 system in the water-gas shift reaction: CO conversion was measured at the beginning and after 21 h of time on stream at 453 K. As previously reported [16] samples prepared on sulfated zirconia are more stable than the corresponding catalysts on plain zirconia. For example the 1AuZSn catalyst preserves a conversion of 87% after 21 h of reaction at 453 K.…”
Section: Samplementioning
confidence: 98%
See 1 more Smart Citation
“…31,54 However, a far less detailed description of the relationship existing between nanostructural properties of the Au surface atoms and their chemisorptive behavior could be deduced from them.…”
Section: ç 3 Nanostructural Analysis Of the Au Sites For Co Adsorptionmentioning
confidence: 99%
“…Characteristics such as surface area, presence of surface hydroxyl groups, density of defects, modification of the surface acidity and of the predominant crystalline phase can influence its adsorption ability [1]. We have recently focused our attention on gold based catalysts supported on zirconia [6,7]. The choice of zirconia as support is due to its intrinsic chemical and physical characteristics that can be adjusted by choosing different precursors and synthesis conditions.…”
Section: Introductionmentioning
confidence: 99%